1997
DOI: 10.2331/suisan.63.145
|View full text |Cite
|
Sign up to set email alerts
|

Spawning Behavior and Selection of Spawning Substrate.

Abstract: In order to elucidate the selection of spawning substrate by female cuttlefish Sepia esculenta, their behavior and trigger stimulus during a spawning sequence were examined in indoor tanks. Fe male approaches substrate, spurts water towards substrate, takes sediment in arms, covers eggs with sediment, spurts water towards substrate again, and undergoes egg deposition on substrate to complete one spawning. Females which finished copulation were visually attracted to more visible substrate. The height of a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cuttlefish are ready to spawn immediately after mating (Watanuki and Kawamura, 1999). Female cuttlefishes (S. esculenta) were observed approaching the spawning substrate (branches of plants or nets of basket traps; Fujita et al, 1997), for placing eggs, one at a time, about every 5 min during an egg-laying session and producing 23-65 egg capsules during a single egg-laying period (Watanuki et al, 2000). Throughout this process, a male accompanied the female (Soichi, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Cuttlefish are ready to spawn immediately after mating (Watanuki and Kawamura, 1999). Female cuttlefishes (S. esculenta) were observed approaching the spawning substrate (branches of plants or nets of basket traps; Fujita et al, 1997), for placing eggs, one at a time, about every 5 min during an egg-laying session and producing 23-65 egg capsules during a single egg-laying period (Watanuki et al, 2000). Throughout this process, a male accompanied the female (Soichi, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its wide distribution and high commercial value, the reproductive biology of S. esculenta is poorly understood, and our knowledge currently consists only of the number of spermatophores [34]; the fecundity of the females (Yasuda [35] reported from the coast of Ise and Mikawa Bay and the seas near Atsumi; Tomiyama [36] reported from the Yamaguchi Prefecture coastal waters; Arima et al [37] reported from the Fukuoka Prefecture coastal waters; and Zhang et al [38] reported from the Qingdao coastal waters); the ripe egg diameter (reported in the Qingdao coastal waters by Zhang et al [38]); the oogenesis (data obtained from a cultured population by Yin et al [29]); and the seminal receptacle's histological structure (reported in the Qingdao coastal waters by Wang et al [39]). Other studies related to the reproductive biology of the species have focused on reproductive behaviour [40][41][42][43]. This study provided data on the morphology of male and female reproductive systems; the number of spermatophores; the spermatophore length and morphology; the ontogenetic changes in spermatophores and spermatophore production; the fecundity of females; the oocyte-phase distribution; the proportion of resorbing oocytes; the histological structure of the ovary; the spermatangia length/structure; and the implantation type of S. esculenta in Japanese waters.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method has not been tried because of the various difficulties involved in such a method. In the laboratory, the spawning behavior of cuttlefish has been reported, 6–8 but not the behavior of cuttlefish via‐á‐vis fishing gear.…”
Section: Introductionmentioning
confidence: 99%